Endogenous Biosynthesis of S-Nitrosoglutathione From Nitro-Fatty Acids in Plants - Mata-Pérez, Capilla (Front Plant Sci, 2020)
Nitro-fatty acids (NO(2)-FAs) are novel molecules resulting from the interaction of unsaturated fatty acids and nitric oxide (NO) or NO-related molecules. In plants, it has recently been described that NO(2)-FAs trigger an antioxidant and a defence response against stressful situations. Among the properties of NO(2)-FAs highlight the ability to release NO therefore modulating specific protein targets through post-translational modifications (NO-PTMs). Thus, based on the capacity of NO(2)-FAs to act as physiological NO donors and using high-accuracy mass-spectrometric approaches, herein, we show that endogenous nitro-linolenic acid (NO(2)-Ln) can modulate S-nitrosoglutathione (GSNO) biosynthesis in Arabidopsis. The incubation of NO(2)-Ln with GSH was analyzed by LC-MS/MS and the in vitro synthesis of GSNO was noted. The in vivo confirmation of this behavior was carried out by incubating Arabidopsis plants with (15)N-labeled NO(2)-Ln throughout the roots, and (15)N-labeled GSNO (GS(15)NO) was detected in the leaves. With the aim to go in depth in the relation of NO(2)-FA and GSNO in plants, Arabidopsis alkenal reductase mutants (aer mutants) which modulate NO(2)-FAs levels were used. Our results constitute the first evidence of the modulation of a key NO biological reservoir in plants (GSNO) by these novel NO(2)-FAs, increasing knowledge about S-nitrosothiols and GSNO-signaling pathways in plants.